DOCTOR OF MEDICINE JACOB REINEGGS ON SHAMKHALATE OF TARKI - Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2019)
The article presents a historiographic analysis of information about Shamkhalate of Tarki, collected by Jacob Reineggs. In his work “Allegemeine historisch-topographische Beschreibund des Kaukasus” (“General Historical and Topographical Description of the Caucasus”), published post-mortem in the German language in 1796, two paragraphs (47 and 48) are dedicated to Shamkhalate of Tarki. In paragraph 47 Reineggs briefly dwells on the Shamkhals, who ruled over this domain in the 18th century, from where it had been reported on their relations with Russia, Persia and Turkey, as well as on a civil strife in Shamkhalate. Paragraph 48 describes the domain itself: its borders, settlements, household, its capital Targu, features of the Shamkhalate relations with dependent and neighbouring domains and rural communities. Relevance of the work lies in the need for a critical analysis of the information provided by the author of the work. Reineggs, who visited the Caucasus five times, is often cited as a source of information on the medieval history of Dagestan. The study of the J. Reineggs’ text was carried out by comparing the author’s information with the information about the Shamkhalate of Tarki from other sources. The analysis has shown that the author made incorrect assertions about the reasons for the change of the capital of Shamkhalate of Tarki; about robberies of the local population being one of their activities; about the particular language of the residents of Karabudakhkent, in the description of Areak (Arakana) and Erpeli as villages whose population spoke one language intrinsic only to them. Nevertheless, the "General Historical and Topographical Description of the Caucasus" is regarded by the author of the article as a good source on the history of Shamkhalate of Tarki, as it was written by a traveler based on his personal impressions.